A Good Life for Laboratory Rodents?. (20th April 2020) - Makowska, I Joanna; Weary, Daniel M
Abstract: Most would agree that animals in research should be spared "unnecessary" harm, pain, or distress, and there is also growing interest in providing animals with some form of environmental enrichment. But is this the standard of care that we should aspire to? We argue that we need to work towards a higher standard—specifically, that providing research animals with a "good life" should be a prerequisite for their use. The aims of this paper are to illustrate our vision of a "good life" for laboratory rats and mice and to provide a roadmap for achieving this vision. We recognize that several research procedures are clearly incompatible with a good life but describe here what we consider to be the minimum day-to-day living conditions to be met when using rodents in research. A good life requires that animals can express a rich behavioral repertoire, use their abilities, and fulfill their potential through active engagement with their environment. In the first section, we describe how animals could be housed for these requirements to be fulfilled, from simple modifications to standard housing through to better cage designs and free-ranging options. In the second section, we review the types of interactions with laboratory rodents that are compatible with a good life. In the third section, we address the potential for the animals to have a life outside of research, including the use of pets in clinical trials (the animal-as-patient model) and the adoption of research animals to new homes when they are no longer needed in research. We conclude with a few suggestions for achieving our vision.